The RNA Methyltransferase METTL3 Promotes Endothelial Progenitor Cell Angiogenesis in Mandibular Distraction Osteogenesis via the PI3K/AKT Pathway - Jiang, Weidong; Zhu, Peiqi; Huang, Fangfang; Zhao, Zhenchen; Zhang, Tao; An, Xiaoning; Liao, Fengchun; Guo, Lina; Liu, Yan; Zhou, Nuo; Huang, Xuanping (Frontiers in Cell and Developmental Biology, 2021)
Distraction osteogenesis (DO) is an approach that has been used in clinical settings to treat large bone defects in oral and maxillofacial surgery. The successful regeneration of bone during DO is dependent upon angiogenesis, and endothelial progenitor cells (EPCs) are key mediators of angiogenic processes. The N6-methyladenosine (m6A) methyltransferase has been identified as an important regulator of diverse biological processes, but its role in EPC-mediated angiogenesis during DO remains to be clarified. In the present study, we found that the level of m6A modification was significantly elevated during the process of DO and that it was upregulated in the context of EPC angiogenesis under hypoxic conditions, which was characterized by increased METTL3 levels. After the knockdown of METTL3 in EPCs, m6A RNA methylation, proliferation, tube formation, migration, and chicken embryo chorioallantoic membrane (CAM) angiogenic activity were inhibited, whereas the opposite was observed upon the overexpression (OE) of METTL3. Mechanistically, silence METTL3 reduced the level of VEGF, PI3Kp110 and the phosphorylation of AKT, while METTL3 overexpression had the opposite effect. In addition, activate AKT phosphorylation by SC79 could restore angiogenic capability of METTL3 deficient EPCs in vitro and ex vivo. METTL3-overexpressing EPCs were additionally transplanted into the DO callus, significantly enhancing bone regeneration as evidenced by improved radiological and histological manifestations in a canine mandibular DO model after consolidation over a 4-week period. Overall, these results indicated that METTL3 accelerates bone regeneration during DO by enhancing EPC angiogenesis via the PI3K/AKT pathways.